Efficacy of Respiratory Training in Relieving Postoperative Pain in Patients with Spinal Nerve Root Entrapment Syndrome. (22nd July 2022) - Hu, Ling; Hu, Liqiong; Xu, Jinglin; Zhang, Zhang; Wu, Jun; Xiang, Yun; He, Qianqian; Zhang, Ting; Li, Jun
Abstract : Background . Breathing exercise can help patients with dyspnea to change the wrong breathing pattern, improve the degree of freedom of respiratory muscles, increase alveolar ventilation, promote breathing, and relieve the symptoms of dyspnea patients. Therefore, this study is aimed at investigating the role of breathing training in alleviating postoperative pain in patients with spinal nerve root entrapment syndrome. Objective . To explore the effect of respiratory training in relieving postoperative pain in patients with spinal nerve root entrapment syndrome. Methods . Fifty-eight patients with spinal nerve root entrapment syndrome treated in our hospital from May 2020 to May 2021 were analyzed retrospectively. The patients were randomly divided into a control group (n = 29 ) and an observation group (n = 29 ). The control group was given routine postoperative pain nursing, and the observation group was given respiratory training on the basis of the control group. The scores of visual analogue scale (VAS), self-rating anxiety scale (SAS), Oswestry dysfunction index questionnaire (ODI), the dosage of postoperative analgesics, and the time of first out-of-bed activity were recorded before pain nursing intervention and 3 days and 7 days after intervention. Results . The VAS, SAS, and ODI scores of the observation group after 3 d and 7 d of intervention were lower than those of the control group. Compared with the same group, the scores of VAS, SAS, and ODI after 3 d and 7 d of intervention were lower than those before intervention, and those after 7 d of intervention were lower than those after 3 d of intervention (P < 0.05 ). The dosage of postoperative analgesics and the time of first out-of-bed activity in the observation group were lower than those in the control group (P < 0.05 ). Conclusion . Respiratory training can effectively relieve postoperative pain, reduce anxiety, and improve spinal function in patients with spinal nerve root entrapment syndrome, which is beneficial to the prognosis of patients and is worthy of promotion.